Influence of Ti-V content on (CrAlTiV)N coating : structure and corrosion response (2024)
(CrAlTiV)N coatings were deposited by DC magnetron sputtering on AISI H13 steel substrates at various Ti-V contents. The microstructural evolution, chemical phases and composition of coatings, were studied systematically by scanning, atomic force and transmission microscopies, energy dispersive x-ray spectroscopy and x-ray diffraction. The corrosion response of the coatings was evaluated by electrochemical impedance spectroscopy and potentiodynamic polarization techniques. Crystalline structures of CrAlN and CrAlTiVN were developed. The morphology of pyramidal tips disappeared, increasing the densification of the coatings and decreasing their roughness and the grain size as their amount of Ti/V increased. An evident protection of AISI H13 steel against corrosion was presented in all coating systems, which were characterized by their dielectric behavior. The formation of the ternary nitride phase Ti3AlN in the (CrAlTiV)N-10.2 at% coating, contributed to this having the best corrosion performance, while the formation of the superconductive nitride VN in the (CrAlTiV)N-14.0 at% coating led to an increase in its conductivity despite its apparently compact structure.